Prevention and Management of Donor-transmitted Cancer After Liver Transplantation: Guidelines From the ILTS-SETH Consensus Conference. Issue 1 (13th December 2021) - Domínguez-Gil, Beatriz; Moench, Kerstin; Watson, Christopher; Serrano, M. Trinidad; Hibi, Taizo; Asencio, José M.; Van Rosmalen, Marieke; Detry, Olivier; Heimbach, Julie; Durand, François
Abstract : As with any other intervention in health, liver transplantation (LT) entails a variety of risks, including donor-transmitted cancers (DTCs). At present, 2%–4% of used deceased organ donors are known to have a current or past history of malignancy. The frequency of DTCs is consistently reported at 3–6 cases per 10 000 solid organ transplants, with a similar frequency in the LT setting. A majority of DTCs are occult cancers unknown in the donor at the time of transplantation. Most DTCs are diagnosed within 2 y after LT and are associated with a 51% probability of survival at 2 y following diagnosis. The probability of death is greatest for DTCs that have already metastasized at the time of diagnosis. The International Liver Transplantation Society-Sociedad Española de Trasplante Hepático working group on DTC has provided guidance on how to minimize the occurrence of DTCs while avoiding the unnecessary loss of livers for transplantation both in deceased and living donor LT. The group endorses the Council of Europe classification of risk of transmission of cancer from donor to recipient (minimal, low to intermediate, high, and unacceptable), classifies a range of malignancies in the liver donor into these 4 categories, and recommends when to consider LT, mindful of the risk of DTCs, and the clinical condition of patients on the waiting list. We further provide recommendations to professionals who identify DTC events, stressing the need to immediately alert all stakeholders concerned, so a coordinated investigation and management can be initiated; decisions on retransplantation should be made on a case-by-case basis with a multidisciplinary approach.